2010
DOI: 10.1128/jvi.01774-09
|View full text |Cite
|
Sign up to set email alerts
|

The Minor Envelope Glycoproteins GP2a and GP4 of Porcine Reproductive and Respiratory Syndrome Virus Interact with the Receptor CD163

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) contains the major glycoprotein, GP5, as well as three other minor glycoproteins, namely, GP2a, GP3, and GP4, on the virion envelope, all of which are required for generation of infectious virions. To study their interactions with each other and with the cellular receptor for PRRSV, we have cloned each of the viral glycoproteins and CD163 receptor in expression vectors and examined their expression and interaction with each other in transfected cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
168
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(177 citation statements)
references
References 54 publications
2
168
0
1
Order By: Relevance
“…Therefore, the amino acid substitutions located within the various ectodomains may have direct and indirect effects on interactions with host cells, as well as associations between the viral structural proteins. Consistent with our findings, a recent published study on porcine reproductive and respiratory syndrome virus has shown that interglycoprotein interactions are critical for mediating interactions with the receptor responsible for virus entry into host cells (15). Specifically, a strong interaction between GP4 and GP5 has been demonstrated, as well as weak interactions among other minor envelope proteins, resulting in the formation of a multiprotein complex.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, the amino acid substitutions located within the various ectodomains may have direct and indirect effects on interactions with host cells, as well as associations between the viral structural proteins. Consistent with our findings, a recent published study on porcine reproductive and respiratory syndrome virus has shown that interglycoprotein interactions are critical for mediating interactions with the receptor responsible for virus entry into host cells (15). Specifically, a strong interaction between GP4 and GP5 has been demonstrated, as well as weak interactions among other minor envelope proteins, resulting in the formation of a multiprotein complex.…”
Section: Discussionsupporting
confidence: 78%
“…Monolayer cultures of HeLa and HEK293 cells were maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and the antibiotics penicillin (100 units/ml), kanamycin (20 units/ml), and streptomycin (20 units/ml) (PKS). Baby hamster kidney (BHK-21) cells were maintained as described earlier (16). The NPeGFPL stable cell line (47) derived from 293 cells was maintained as described before (47) in the presence of 1 mg/ml G418.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, this is the first time these results have been reported in the literature. Specifically, previous studies demonstrated that the minor envelope glycoproteins GP2 and GP4 of PRRSV interacted with pCD163 (51,52). The glycosylation of the GP2 and GP4 proteins was also shown to be required for efficient PRRSV interaction with the receptor (53,54).…”
Section: Pcd163 Srcr5 Structure For Prrsv Infectionmentioning
confidence: 99%